Peningkatan Hasil Belajar IPA Ciri-Ciri Hewan melalui Penggunaan Media Gambar pada Kelas VI A SDN 61/X Talang Babat - Bustami Bustami (Jurnal Gentala Pendidikan Dasar, 2020)
This study aims to improve the learning outcomes of animal characteristics material through the media of images in grade VI A SD Negeri 61 / X Talang Babat. This research is a classroom action action (PTK). This research consisted of 2 cycles. The stages of each cycle are the stages of planning, observing, observing and reflecting on actions. The research subjects were students of class VI.A SDN 61 / X Talang Babat, Muara Sabak Barat District, Tanjung Jabung Timur Regency, with a total of 35 students consisting of 18 boys and 17 girls. The data of this research are text and numbers regarding the understanding of the learning outcomes of animal characteristics. Observation data through and tests. The result of the research states that the improvement of student learning outcomes includes cognitive, affective and psychomotor aspects. This can be seen in the improvement of learning outcomes through written test scores. Based on the results of the written test when the learning process obtained the following results: in the first cycle the average score of the written test was 60.57 and 24 children or 68.57% of the total students had completed, while only 11 children or 31.43 were left incomplete %. In Cycle II the average written test increased from 60.57 to 80.00. Students who have completed in the first cycle are 24 children, increasing to 32 children or 68.57% to 91.43%. Meanwhile, the number of students who did not complete it decreased from 11 students to only 3 students.